Identifikasi Sebaran Intrusi Air Laut Melalui Profil Kualitas Air Sumur Di Pantai Barombong - Nurnawaty; M. Agusalim; Muh. Nurul Fitrah S; Ranum Indah Putri (Jurnal Karajata Engineering, 2025)
Rapid development in Makassar City increases the demand for housing, clean water and industry, which encourages massive exploitation of groundwater. If this continues, it could degrade groundwater quality and quantity and trigger seawater intrusion, threatening groundwater availability in the region. The aim of this research is to analyze and identify measurements and values of salinity due to sea water on ground water quality at Barombong Beach. In this research, a research l ocation survey was carried out, sampling stage, sample testing stage, data processing stage, community interview stage. The well water at Barombong Beach has a salinity that is still categorized as fresh to brackish. Well water that has a salinity of <0.5% then the water is categorized as fresh, >0.5-30%, then the water is categorized as brackish and if the water salinity is >40% then the water is detected as salty. From the results of this research calculation, the highest salinity is found in well 15, namely 5% at a distance of 858.76 from the shoreline and the lowest is located at wells 1 and 2, namely 0.2% which is located at a distance of 165.98 m and 201.06 m from the shoreline.